2016
DOI: 10.1371/journal.pone.0146498
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Deep Bisulfite Sequencing to Detect Specific DNA Methylation Patterns of Minor Cell Types in Heterogeneous Cell Populations: An Example of the Pituitary Tissue

Abstract: DNA methylation is an epigenetic modification important for cell fate determination and cell type-specific gene expression. Transcriptional regulatory regions of the mammalian genome contain a large number of tissue/cell type-dependent differentially methylated regions (T-DMRs) with DNA methylation patterns crucial for transcription of the corresponding genes. In general, tissues consist of multiple cell types in various proportions, making it difficult to detect T-DMRs of minor cell types in tissues. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Since each read in a WGBS library is the clonal derivative of a DNA molecule originating from a single cell, cell-specific information is inherent in WGBS data 27 , as it is in clonal BS-seq. The use of read-level bisulfite sequencing data to infer cell type- and allele-specific methylation patterns is well established in the literature 28,29 , though until now it has not yet been deployed on a genome-wide scale.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since each read in a WGBS library is the clonal derivative of a DNA molecule originating from a single cell, cell-specific information is inherent in WGBS data 27 , as it is in clonal BS-seq. The use of read-level bisulfite sequencing data to infer cell type- and allele-specific methylation patterns is well established in the literature 28,29 , though until now it has not yet been deployed on a genome-wide scale.…”
Section: Resultsmentioning
confidence: 99%
“…To begin to understand downstream, cell type-specific effects, we implemented a read-level analysis of our WGBS data, analogous to previously described approaches using ultra-deep BS-seq to identify minor cell populations in pituitary tissue 29 . This led us to conclude that TGF-β-associated SMAD binding motifs enriched in hypermethylated DMRs are a signature of secondary effects in non-AgRP cell types, and that specific hypomethylated read clusters in the promoter region of Bmp7 originate from AgRP neurons.…”
Section: Discussionmentioning
confidence: 99%
“…This strongly suggested that DNA methylation is at least in part related to transcriptional repression of FBN1 . To further examine the correlation between DNA methylation and FBN1 expression, the previously proposed Hypo-allele concept [ 27 ] was applied to FBN1 . CpG island shores are involved in the tissue/cell-type-dependent gene expression [ 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…DNA methylation analysis by sodium bisulfite polymerase chain reaction (PCR) followed by sequencing of cloned PCR fragments enabled us to identify DNA methylation patterns of each sequenced fragment that can be recognized as one allele/cell in a tissue. Based on this concept, we previously focused on transcriptionally active DNA hypomethylated alleles (Hypo-alleles), which can be recognized by the high ratio of unmethylated CpGs in each sequenced fragment (allele), and indicated that Hypo-allele ratio of a non-imprinted and autosomal gene can be used to estimate the proportion of the cell type expressing the corresponding gene in the tissue [ 27 ]. Therefore, the Hypo-allele concept can be applied to the detection of transcriptional regulation in each allele involved in certain tissues or cell populations.…”
mentioning
confidence: 99%
“…Another method, epiG [12], does utilize methylation patterns in WGBS reads, but identifies only one dominant epi-haplotype in each sample, essentially disregarding cell type heterogeneity. Other attempts at exploring readlevel information in WGBS data sets have focused on minority regions such as those exhibiting "bipolar methylation" [13] or containing "hypo-methylated alleles" [14], rather than assessing the full breadth and depth of potential cell type-specific signals.…”
Section: Introductionmentioning
confidence: 99%